Application of the Time Step Optimization Method in Seismic Liquefaction Analysis and Its Evaluation Method for Computational Efficiency Improvement - Qi Li; Bin Li; Shaorui Sun; Nan Yang (Shock and Vibration)
In order to solve the time step setting problem in seismic liquefaction numerical analysis, the time step optimization method was introduced into seismic liquefaction numerical analysis platform, and the seismic response of earth dam was analyzed. The results show that the time step optimization method can effectively solve the time step setting problem. In addition, in order to evaluate the computational efficiency improvement of the optimized seismic response, a new method was proposed, and an example with analytical solution was selected to verify it. And the proposed method was used to evaluate the calculation efficiency of the optimized seismic response. The results show that the computing efficiency is greatly improved after the seismic liquefaction numerical analysis program is optimized by the time step optimization method.